The Distribution of Top Incomes in Australia. - Atkinson, A; Leigh, A (Centre for Economic Policy Research (Australian National University), 2006)
Using taxation statistics, we estimate the income share held by top income groups in Australia over the period 1921-2003. We find that the income share of the richest fell from the 1920s until the mid-1940s, rose briefly in the postwar decade, and then declined until the early 1980s. During the 1980s and 1990s, top income shares rose rapidly. At the start of the twenty-first century, the income share of the richest was higher than it had been at any point in the previous 50 years. Among top income groups, recent decades have also seen a rise in the share of top income accruing to the super-rich. Trends in top income shares are similar to those observed among other elite groups, such as judges, politicians, top bureaucrats and chief executive officers.